2016
DOI: 10.1002/andp.201600098
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of photonic nanojets in 3D dielectric cuboids excited by surface plasmons

Abstract: In this paper we study the excitation of photonic nanojets (PNJ) in 3D dielectric cuboids by surface plasmons at telecommunication wavelengths. The analysis is done using the effective refractive index approach. It is shown that the refractive index contrast between the regions with and without cuboid should be roughly less than 2 in order to generate jets at the output of the cuboid. The best performance at λ 0 = 1550 nm is obtained when the height of the cuboid is 160 nm producing a jet just at the output in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…As in refs. [], a non‐uniform mesh with a maximum cell size of 1/5λ 0 at the dielectric‐metal interface was applied. All the field distributions shown below are normalized by their maximum values.…”
Section: Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…As in refs. [], a non‐uniform mesh with a maximum cell size of 1/5λ 0 at the dielectric‐metal interface was applied. All the field distributions shown below are normalized by their maximum values.…”
Section: Modelingmentioning
confidence: 99%
“…Moreover, the SPP PJ is moved away from the cuboid as it is enlarged. It was also demonstrated that it is possible to detect subwavelength (0.1 λ) metal particles by means of plasmonic PJ . Lately, it was shown that the SPP PJ performance can be engineered by simply changing the height of the dielectric at the operation wavelength for the flat disk, cuboid, and also with the plasmonic lenses …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extra ordinary enhanced transmission through subwavelength metallic structures such as slits and holes have been reported by numerous researchers in the last decade [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. One of the typical works is the presentation regard ing the control of beaming through the subwavelength metallic slits reported by Yu et al in Ref.…”
Section: Introductionmentioning
confidence: 99%